Improving Output Voltage of the Three Phase Six-Switch Inverters - Ebrahim Babaei; Mehdi Mahaei (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
In this paper, a simple method for selecting the best conductive angle based on power factor of load in three phase six-switch inverters is proposed. Conductive angle from 120º to 180º, and power factor from 0 to 1 are changed for lead and lag loads. Then RMS and THD values of the output voltage are studied. Simulation results show that a special conductive angle for each specific power factor has to be used to improve the mentioned indices and applying conventional conductive angles 120º, 180º and 150º in some power factors increases THD and decreases RMS of output voltage.